Bioethics and Pharmacology : Ethics in Preclinical and clinical Drug Development - Todorovic, Zoran; Prostran, Milica; Turza, Karel (Kerala, India : Transworld Research Network, 2012)
This book is the result of impressive progress in developing bioethics in Southeast Europe during the last decade. Bioethical ideas of Van Rensselaer Potter and Fritz Jahr lie along the same continuum with a concept of integrative bioethics. It was born in Mali Lošinj, Croatia ten years ago, where the international conference entitled Lošinj Days of Bioethics - Integrative Bioethics and New Epoch has been held since 2001. In recent years, the holy mission of the Conference has been fulfilled. Integrative bioethics has been widely adopted in the region, both in academic institutions and in the general public. It is incorporated into the curricula of different faculties from biology and medicine to philosophy and law. More importantly, it has attracted a significant number of students and become the issue of public interest per se. Bioethical panels are well attended, and there is a sustained increase in number of bioethical publications, mainly books and journals in the region. An important issue in contemporary bioethics is animal welfare, which has undergone enormous changes in the past twenty years. The integrative bioethics, in its essence, is based on pluriperspectivism of different viewpoints, from philosophy, sociology, psychology and law to medicine, biology, economics, technology, demographics, politics, religion, ecology and art. It successfully overcomes the gap between scientific advances and humanities in such a way that builds key pillars towards a sustainable future. Another keyword that best describes the integrative bioethics is communication. It is not just an exchange of information between living organisms. At a broader level, it also involves their relationships with the environment. In addition, bioethics provides an opportunity to find a common language with different people, which is of particular importance for the communication in Southeast Europe at the beginning of the 21st century. Drug discovery and development, as well as their medical use have always been a matter of debate. There is a wide range of opposing viewpoints towards pharmacotherapy, from the uncritical expectations and beliefs in its omnipotence, to denial and disappointment. According to a survey conducted by the British Medical Journal staff in 2007, four out of ten most important achievements in the history of medicine in the last 150 years were drugs (antibiotics, anaesthesia, vaccines and hormonal contraceptives). At the same time, pharmaceutical companies have come under intense criticism because they spend huge amounts of money on drug research and development. In addition, the role of complementary and alternative medicine in health care system still remains to be established. Drug development is a complex and long term process that raises numerous bioethical issues. For example, there are more questions than answers with regard to ethics of animal testing of medicines and vaccines, use of genetically modified organisms, clinical trials in vulnerable groups, and development of biopharmaceutical drugs. This book is not intended (just) to provide ethical guidelines to problem solving and decision making. Rather, it should foster a positive attitude towards pluriperspective approach to moral dilemmas in medicine.
Bibliografija na kraju svakog poglavlja
Keywords: bioetika; farmakologija; lijekovi -- testiranje na životinjama